Revisiting the Dark Triad Dirty Dozen (DTDD) in Indonesian Population: Examining Factor Structure Using CFA and ESEM - Nugraha, Ahmad Helmi; Jatnika, Ratna; Abidin, Zainal; Hanami, Yuliana; Karl Jonason, Peter (Psympathic : Jurnal Ilmiah Psikologi, 2025)
This research aimed to investigate the structural validity of the Dark Triad Dirty Dozen (DTDD) within the Indonesian cultural context. At the preliminary stage, content validity and response process were assessed as part of a systematic translation verification to ensure item clarity and conceptual relevance. Even though satisfactory performance was reported, items 3 and 10 required further cultural refinement. Structural models were also tested using Confirmatory Factor Analysis (CFA) and Exploratory Structural Equation Modelling (ESEM). The results showed that the three-factor structures of Machiavellianism, Narcissism, and Psychopathy were supported as the most conceptually sound and statistically stable option. The bifactor solution reported interpretive limitations, such as low item loadings even though alternative models suggested acceptable fit. Subsequently, ESEM captured subtle cross-loadings, stating the psychological overlap between traits. These results supported the suitability of DTDD and offered an enhanced understanding of the structural complexity of dark traits to strengthen the relevance of cross-cultural personality assessment.